2022
DOI: 10.2147/ijn.s384592
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes as Carriers in Drug Delivery for Non-Small Cell Lung Cancer, Mechanistic Analysis of Their Carcinogenic Potential, Safety Profiling and Identification of Biomarkers

Abstract: Non-small cell lung cancer (NSCLC) is a global burden leading to millions of deaths worldwide every year. Nanomedicine refers to the use of materials at the nanoscale for drug delivery and subsequent therapeutic approaches in cancer. Carbon nanotubes (CNTs) are widely used as nanocarriers for therapeutic molecules such as plasmids, siRNAs, antisense agents, aptamers and molecules related to the immunotherapy for several cancers. They are usually functionalized and loaded with standard drug molecules to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 131 publications
(200 reference statements)
0
7
0
Order By: Relevance
“…Among CNTs, the average diameters of SWCNTs range between 0.4 and 2 nm, whereas the diameters of DWCNTs and MWCNTs range between 2 and 100 nm, and 1 and 3.5 nm, respectively. , The size of MWCNTs and SWCNTs functionalized or loaded with anticancer drugs range between 5 and 700 nm for effects on in vitro cell lines. In vivo , the diameters may vary from 20 to 50 nm …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among CNTs, the average diameters of SWCNTs range between 0.4 and 2 nm, whereas the diameters of DWCNTs and MWCNTs range between 2 and 100 nm, and 1 and 3.5 nm, respectively. , The size of MWCNTs and SWCNTs functionalized or loaded with anticancer drugs range between 5 and 700 nm for effects on in vitro cell lines. In vivo , the diameters may vary from 20 to 50 nm …”
Section: Resultsmentioning
confidence: 99%
“…In vivo, the diameters may vary from 20 to 50 nm. 70 3.6. Synthesis Methods and Characterization Techniques for CNTs.…”
Section: Diagnosis and Existingmentioning
confidence: 99%
“…CNTS are considered important candidates for drug delivery due to their needle-like structure, biocompatibility, and high surface area [ 216 ]. A drug molecule can be delivered via CNTs in three ways: 1. drugs can be encapsulated in CNT cavities; 2. drugs can be conjugated using chemical tethers; 3. drugs can be linked to CNT amines or carboxylic acids [ 217 ].…”
Section: Application Of Nanoparticles To Improve the Therapeutic Pote...mentioning
confidence: 99%
“…Evidence has suggested that nanomedicine could enhance immunotherapy in NSCLC (Seshadri and Ramamurthi, 2018;Garcia-Fernandez et al, 2020;Pu et al, 2022). For example, TME component-targeted nanomedicine delivery facilitated the efficacy of immune checkpoint inhibitors (Kim et al, 2021).…”
Section: Nanomedicine Enhances Immunotherapy In Lung Cancermentioning
confidence: 99%